Efektivitas Edukasi Kesehatan Reproduksi Berbasis Evidence-Based Education Terhadap Peningkatan Pengetahuan Dan Sikap Remaja Tentang Risiko Kehamilan Dini: Studi Pre-Experimental Pada Siswa SMP Negeri 1 Unter Iwes, Kabupaten Sumbawa - Ninik Wahyuni; Fitri Setianingsih; Rati Andriani (STIKES Columbia Asia Medan, 2026)
Background: Adolescent pregnancy remains a persistent public health concern with adverse consequences on maternal-neonatal outcomes, educational attainment, and psychosocial well-being. Evidence-based education (EBE) has emerged as a promising strategy for improving reproductive health literacy, yet empirical data from junior high school settings in Eastern Indonesia remain limited. Objective: This study aimed to evaluate the effectiveness of an evidence-based education intervention on improving knowledge and attitudes regarding early-pregnancy risks among adolescents at SMP Negeri 1 Unter Iwes, Sumbawa Regency. Methods: A quantitative pre-experimental study with a one-group pretest–posttest design was conducted. Fifty seventh-grade students were recruited using purposive sampling based on predefined inclusion criteria. Knowledge and attitudes were measured using structured questionnaires before and after the intervention. Data were analyzed using univariate statistics and the Paired Sample t-test at α = 0.05, following a Shapiro-Wilk normality assessment. Results: The proportion of respondents with good knowledge rose from 16% to 70%, and positive attitudes increased from 38% to 82%. Mean knowledge scores improved from 63.20 (pretest) to 84.60 (posttest), while mean attitude scores rose from 64.40 to 79.80. The Paired Sample t-test yielded p = 0.000 (p < 0.05) for both variables, indicating statistically significant improvements. Conclusion: Evidence-based reproductive health education significantly improved adolescents' knowledge and attitudes toward early-pregnancy risks. Integrating evidence-based reproductive health modules into School Health Programs (UKS) is recommended as a scalable promotive-preventive strategy.